Intracarotid chemotherapy of glioblastoma after induced blood-brain barrier disruption. - Bonstelle, C T; Kori, S H; Rekate, H (American Journal of Neuroradiology, 1983)
Intracarotid chemotherapy has been suggested as an additional mode of therapy in patients with brain tumors. Seven comatose patients received intracarotid 5-fluorouracil and adriamycin after intracarotid infusion of 25% mannitol to open the blood-brain barrier at the tumor site. Five of seven patients became fully functional for 3-12 months. Another 11 patients entered the study, of which nine are currently receiving therapy and are functional, and two have died, one from brain herniation. The results are encouraging and support the need for further research of this therapeutic method.